Quality and Quantity of Disclosure: The Case of Iranian Listed Companies Implementing Harmonised IASs - Jamal Roudaki (Journal of Accounting, Business and Management (JABM), 2012)
The Tehran Stock Exchange of Iran requires listed companies to submit audited financial statements based on the first National Accounting Standards (NASs). Recently developed NASs, highly harmonised with the International Accounting Standards (IAS), are to be adopted by all companies from 2000. The purpose of this study is to examine the quality and quantity of disclosures in the financial statements of listed companies comparing before and after implementation the NASs. Results indicate that disclosure notes are concentrated on almost half of the NASs while others are neglected. The quantity of the disclosures related to these standards has improved significantly after implementation of the internationally harmonised accounting standards. However, despite the improvement, the overall quality of disclosures is low. Size (positively) and profitability (negatively) are statistically related to the means of the quality of disclosure. The mean of the quality of disclosure increases as the listed companies are audited by private auditors on opposed to government affiliated auditors. Changes in the quality of disclosures are not statistically associated with company-specific characteristics of size, profitability, leverage and auditor-type of the listed companies.